The emergence of the housing affordability gap - McNulty, Paul (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2003)
This paper proposes strongly that housing affordability is a real issue, though it has often been overlooked because it is obscure and by its nature difficult to analyse: it is not as easily explainable as, say, adequate food and clothing - yet it is every bit as important. After all shelter is a basie need. The paper shows that historically affordability of land has been an issue in Ireland for centuries and that recently it has become an acute issue with lasting implications for the future of housing affordabi lity and other areas. Just as the state intervened in housing in the past for collective consumptive rcasons, it may now be necessary for the state to intervene again to prevent continuation of the problem. The paper focuses specifically on capping land prices as a means of improving housing affordability, offering in particular a consideration of the possible implications of implementing the proposals put forward by Justice Kenny in 1973. Although there are of course a number of other possible policy approaches that might bring prices down, such as improving the balance between supply and demand, land taxation, or the capping of lending institutions, these are beyond the scope of Ihis discussion.
Papers from practice
Keywords: Urban geography -- Ireland